2011
DOI: 10.1073/pnas.1016217108
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the curcumin metabolic pathway involving a unique enzyme in an intestinal microorganism

Abstract: Polyphenol curcumin, a yellow pigment, derived from the rhizomes of a plant (Curcuma longa Linn) is a natural antioxidant exhibiting a variety of pharmacological activities and therapeutic properties. It has long been used as a traditional medicine and as a preservative and coloring agent in foods. Here, curcumin-converting microorganisms were isolated from human feces, the one exhibiting the highest activity being identified as Escherichia coli. We are thus unique in discovering that E. coli was able to act o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
164
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(168 citation statements)
references
References 33 publications
2
164
0
2
Order By: Relevance
“…The intestinal tract is thought to play an important role in the metabolic disposition of curcumin [22,23]. Curcumin-metabolizing microorganisms were isolated from human feces, and the purification and characterization of a curcumin-converting enzyme was reported in previous study [23]. However, these previous studies did not provide detailed information about the metabolic pathways affecting curcumin in intestinal bacteria, although curcumin has been taken orally as a food agent or medicine since ancient times.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The intestinal tract is thought to play an important role in the metabolic disposition of curcumin [22,23]. Curcumin-metabolizing microorganisms were isolated from human feces, and the purification and characterization of a curcumin-converting enzyme was reported in previous study [23]. However, these previous studies did not provide detailed information about the metabolic pathways affecting curcumin in intestinal bacteria, although curcumin has been taken orally as a food agent or medicine since ancient times.…”
Section: Discussionmentioning
confidence: 97%
“…The intestinal bacteria model is a useful in vitro tool to predict drug-metabolism pathways in vivo. The intestinal tract is thought to play an important role in the metabolic disposition of curcumin [22,23]. Curcumin-metabolizing microorganisms were isolated from human feces, and the purification and characterization of a curcumin-converting enzyme was reported in previous study [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacologic activity of curcumin is thought to be due to the formation of its metabolite tetrahydrocurcumin by the gut microbiota. Analyses of microorganisms isolated from human feces revealed that Escherichia coli exhibited among the highest curcumin-metabolizing activities (Hassaninasab et al, 2011). The responsible enzyme was identified as CurA, NADPH-dependent curcumin/dihydrocurcumin reductase, which bears similarities to members of the medium-chain dehydrogenase/ reductase superfamily.…”
Section: Impact Of the Microbiota On The Metabolism And Bioavailabilimentioning
confidence: 99%
“…sesamin | metabolism | lignan | tetrahydrofolate W e have been involved in studies of not only microbial metabolism of man-made compounds (1-3) but also biologically active natural compounds, such as curcumin (4). In this study, we characterize the microbial metabolism of the lignan sesamin.…”
mentioning
confidence: 99%